A (IN) SEGURANÇA JURÍDICA QUANTO À SUCESSÃO DA HERANÇA DIGITAL (REMUNOM, 2024)
This article addresses digital inheritance, which has arisen from the constant technological changes affecting society, aiming to expose conceptual aspects of inheritance law and digital inheritance, in addition to identifying bills that aim to regulate the subject. This work addresses the problem of classifying digital assets that can be transferred and the apparent violation of the privacy of the person who is the subject of the transfer of their digital assets, and to what extent it is considered valid to ensure the rights of heirs and testamentaries. The methodology used consists of a literature review, using books, scientific articles, legislation, and monographs. It is believed that such attention to the subject at hand is relevant, since the end of the natural person is inherent to any individual, so that the transfer of their assets also qualifies as an unavoidable act. Therefore, the need to study the subject arises from the imminent need to provoke the legislature to seek solutions for its regulation, in order to pacify the issue and provide legal certainty that currently does not exist in the relationships of transfer of digital assets.